Normalized Difference Vegetation Index Analysis to Evaluate Corn Cultivation Technology Based on Farmer Participation - Fadjry Djufry; Muhammad Farid; Ahmad Fauzan Adzima; Muhammad Fuad Anshori; Amir Yassi; Yunus Musa; Nasaruddin Nasaruddin; Muhammad Aqil; Hari Iswoyo; Muhammad Hatta Jamil; Sakka Pati (Indonesian Journal of Geography, 2022)
An unmanned aerial vehicle (UAV), widely known as a drone, proves very effective in assessing cropping or crop cultivation. Its practical use in evaluating corn cultivation technology systems is feasible when based on farmer participation. UAV can generate the Normalized Difference Vegetation Index (NDVI) algorithm that reflects the greenness of leaves, which is a parameter related to photosynthesis and plant productivity. Therefore, the purpose of this study was to evaluate whether the participation-based UAV-derived NDVI could be effectively used to assess corn cultivation technology and determine the appropriate technology to be used in the cultivation. The research was conducted in Tarowang Village in Galesong Selatan District, Takalar Regency, South Sulawesi, Indonesia, using two plots, namely, mother trial and baby trial. The mother trial applied a randomized block design in which eight packages of corn cultivation technology were randomly assigned, whereas the baby trial consisted of eight corn plots cultivated by farmers. In the latter, each farmer received one package of the cultivation technology. The study results indicated that NDVI and yield could effectively evaluate corn cropping. Three packages, i.e., P1, P4, and P5, are recommended for corn cultivation, especially in the village observed. Nevertheless, they are expected to be also applicable to other districts in South Sulawesi to promote improvement in corn production.